[tex]\bf 4~~,~~\stackrel{4+6}{10}~~,~~\stackrel{10+6}{16}~~,~~...~\hspace{10em}\stackrel{\textit{common difference}}{d = 6} \\\\[-0.35em] ~\dotfill\\\\ n^{th}\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} a_n=n^{th}\ term\\ n=\textit{term position}\\ a_1=\textit{first term}\\ d=\textit{common difference}\\[-0.5em] \hrulefill\\ a_1=4\\ d = 6 \end{cases} \implies a_n=4+(n-1)6 \\\\\\ a_n=4-6+6n\implies a_n=6n-2~\hfill \displaystyle\boxed{\sum\limits_{n = 1}^{7}~6n-2}[/tex]